DOI: 10.18297/etd/1588
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of nanoparticles with dielectrophoretic nano-probes.

Abstract: negative dielectrophoresis repels particles from the region of the highest electric field gradient. The dielectrophoretic force is directly proportional to the square of the electric field gradient, as well as the cube of the radius of the particles involved.As particles decrease in size, the gradient of the electric field must increase rapidly in order to capture or repel the particles. The intense electric field gradients were produced using fabricated silver gallium (Ag 2 Ga) nano-probes electrodes in conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…For concentrating and killing smaller viruses, studies focus on 3D nano-electrode arrays with carbon nanotubes that create extremely high electric field strengths at the tips [ 17 , 35 , 69 ]. A few studies have demonstrated that micro-channels can be used to generate high electric fields by controlling the channels width.…”
Section: Electrode Configurations For Trapping Sampling and Killingmentioning
confidence: 99%
“…For concentrating and killing smaller viruses, studies focus on 3D nano-electrode arrays with carbon nanotubes that create extremely high electric field strengths at the tips [ 17 , 35 , 69 ]. A few studies have demonstrated that micro-channels can be used to generate high electric fields by controlling the channels width.…”
Section: Electrode Configurations For Trapping Sampling and Killingmentioning
confidence: 99%